Research on Multi-Mode Operation and Coordinated Control Strategy of Grid-Connected Photovoltaic/Biogas/Energy-Storage System for Rural Ecological Breeding - Zhang, Xinhe; He, Guixiong; Xiong, Junjie; He, Wei; Xiao, Changlin (Frontiers in Energy Research, 2022)
Driven by the rural revitalization strategy and the carbon neutrality goals, the grid-connected photovoltaic/biogas/energy-storage (PV/biogas/ES) system is increasingly widely used in rural China. In this paper, a coordinated operation and control strategy of grid-connected PV/biogas/ES system for rural ecological breeding is proposed. Biogas, ES, and controllable load can adjust their operation state based on meeting constraint conditions to prevent overload from affecting the distribution transformer service life. The line voltage and load can adjust the ES control strategy. The peak shaving and valley filling can be realized through orderly charge/discharge control, in normal operation. Based on virtual synchronous generator (VSG) control, the ES has a certain frequency modulation ability. Meanwhile, overcharge, and over discharge can be avoided by detecting the state of charge (SOC) and adjusting the output power. When the line voltage drops suddenly, VSG can be switched to reactive power compensation mode. The battery energy storage system (BESS) and grid-connected inverter constitute a STATCOM/BESS, which can provide continuous reactive current to the grid to raise the line voltage and improve the system reliability. The effectiveness of the proposed strategy is verified by MATLAB/Simulink simulation.